(untitled) (Research, Society and Development, 2022)
The community of Boa Vista do Acará portrays the characteristics of a riverside community typical of the Amazon region, it has a forest context with spaces for permanence and changes due to the "introduction of the water economy and the mineral economy, giving rise to a typology of territories with different economic, social, environmental and cultural forms and dynamics". Research on safety at work and conditions of the work environment becomes relevant in the understanding of daily practices regarding the collection and production of açaí, a reality that is part of the cultural tradition. This requires the observance of ancestral values, habits and customs, therefore, elements of subjectivity of the subjects involved in the research. The sample consisted of 24 members of the Association of Producers in order to obtain data when the issue of safety at work of family farmers, taking as a reference the activities they develop, for this selection, the task and the commitment and responsibility of each associated. The information obtained was associated with the quantitative data obtained from the POBV documents. It was found that it is not enough just for some associates to participate in these events, and for the acquisition of some equipment, without the proper knowledge of which equipment should be acquired and passed on to the associates, due to the occurrence of accidents and the health problems they presented. The traditional method of harvesting is still used in the execution of activities, as well as the use of artisanal tools such as machete, machete, peconha, which without proper preventive knowledge, makes the peconheiro susceptible to accidents and occupational diseases.